The Relationship of Maternal Parenting with the Incidence of Picky Eater in Pre-school Age Children At Tk Tunas Harapan Winduraja Village - Yuyun Rahayu; Ima Sukmawati; Lusi Lestari; Lala Lastri Septiani (Jurnal EduHealth, 2023)
Picky eater is a difficult eating behavior in children by refusing to eat (neophobia), consuming a limited variety of food types, refusing foods that are not liked, and only eating foods they like. Picky eaters in preschool children who last long and continuously have a negative impact on the fulfillment of nutrition and nutrition in children. Maternal parenting is one of the external factors that influence the incidence of picky eaters. Objective: To determine the relationship between maternal parenting and the incidence of picky eaters in pre-school children at Tunas Harapan Kindergarten, Winduraja Village. Methods: The research method is quantitative with cross sectional research design. The sampling technique is total sampling, namely all mothers who have 34 pre-school children. The research instrument was a questionnaire sheet. Data analysis using univariate and bivariate analysis with chi square statistical test. Research results: The highest frequency of maternal parenting is the permissive category as many as 17 people (50.0%). The incidence of picky eaters in preschool children, the highest frequency is experiencing picky eaters as many as 20 people (58.8%). Static test results with chi square test obtained a value of р = 0.000 < α = 0.05 (5%). Conclusion: There is a relationship between maternal parenting and the incidence of picky eaters in preschool children at Tunas Harapan Kindergarten, Winduraja Village with a statistical test p value < α. It is expected that parents, especially mothers, can understand and apply the correct and appropriate parenting, for example, providing a variety of foods so that children do not get bored quickly and have a good appetite.